The never-ending story of compensations for regulatory changes: the Stadtwerke München arbitration - Moreno Molina, Ángel M. (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
Regulatory changes concerning the generation of electricity from renewable sources can produce negative consequences for the economic expectations and for the benefits of the companies that invested in that sector, especially when those regulatory changes lead to a reduction in the price of the electricity produced in those installations. In those cases, ocurring in several countries, the affected firms usually take legal actions in demand for compensation. In the case of Spain, which adopted a controversial regulatory change in this field, numerous lawsuits and international arbitrations have taken place. The case presented here constitutes the latest example of such trend and includes some questions and approaches of extraordinary importance for the future of these conflict resolution mechanisms.